Can AI Universally Help Students and Teachers?: A Cross-Cultural Investigation of Perceptions of AI's Potential in Education - Natthanich Mekadenaumporn (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2025)
As Artificial Intelligence (AI) increasingly advances and permeates our lives, education has been one of the most disrupted sectors. With numerous AI educational tools developed to enhance education, much research has also been done to assess their efficacy, merits and limitations. Nevertheless, past research has shown a striking lack of investigation into educators’ perspectives, which points to their limited representation in discourse about AI in education despite them being such pivotal stakeholders. Additionally, most past research studying public opinion on AI in education has been too general, with an evident lack of clarity in differentiating various types of AI used in each aspect of educators’ job scope, resulting in vague generalised findings. Therefore, to fill these gaps, interviews have been conducted on 22 professional educators to learn about their opinions on AI tools used in education derived from both their own personal experiences and second-hand knowledge. A comprehensive analysis of their responses then reveals valuable insights about areas in education with high potential for AI assistance, inherent limitations of AI, the importance of human educators amidst rapid AI advancement, the varying suitability of applying AI in various educational contexts (subject areas, educational system and academic levels) and the importance of much greater personal involvement of educators in the development of AI tools to optimise their effectiveness in enhancing education.